정유 공장에서 발생된 폐수 슬러지의 최적 감량화 방안 연구 - 최재우; 정종민; 심나타리아; 박철희; 이상협 (대한상하수도학회, 2010)
In this study, anaerobic digestion, electro-oxidation and electro-fenton oxidation processes were investigated to reduce oily refinery sludge. Anaerobic digestion process was not suitable for oily activated sludge reduction because of characteristics itself and, as experimental results revealed, reduction efficiency was low for electro-oxidation process. However, 40% total suspended solid reduction of oily activated sludge was obtained by electro-fenton oxidation process, operating at pH=1, 0.5 A and Fe2+: H2O2 ratio = 1:30. In addition, higher reduction efficiency was obtained as reaction time was increased (30, 60, 90, 120 min) despite of low H2O2 concentration. From the results, it has been investigated that electro-fenton oxidation is efficient process for oily activated sludge reduction.